Profiling students’ mathematical reasoning in the alkhairaat context using rasch analysis: A mixed-methods study - Dewi Sri Wahyuni; Tahril; Dasa Ismaimuza; Pathuddin; Mustamin Idris; Windia Hadi (CV. FOUNDAE, 2026)
Background: Students’ mathematical reasoning is often limited by their difficulty in linking abstract mathematical concepts with meaningful real-life contexts. In many classrooms, mathematics is perceived as disconnected from students’ sociocultural experiences, which can hinder the development of deeper reasoning processes. Aims: This study aims to profile students’ mathematical reasoning abilities within the Alkhairaat sociocultural context and to examine how contextual integration influences reasoning across different ability levels. Method: A sequential explanatory mixed-methods design was employed involving 33 eighth-grade students in a madrasah. Quantitative data were collected through a mathematical reasoning test embedded in the Alkhairaat context and analyzed using the Rasch measurement model (Ministep 5.10.4.0) to evaluate the instrument’s psychometric quality and map students’ reasoning abilities. Qualitative data were then obtained through clinical interviews to explore students’ cognitive processes when solving contextual problems. Results: Rasch analysis indicated acceptable psychometric properties, with item reliability of 0.67 and person reliability of 0.58. Wright Map analysis categorized students into three ability levels: high (12.12%), medium (66.67%), and low (21.21%). The findings show that the Alkhairaat context functions differently across ability levels: as a cognitive tool for abstraction among high-ability students, as procedural scaffolding for medium-ability students, and primarily as an affective anchor for low-ability students. Conclusion: Integrating sociocultural contexts such as Alkhairaat values can support mathematical reasoning by providing meaningful entry points for abstraction. However, its effectiveness depends on students’ initial proficiency, indicating the need for additional instructional support for lower-ability learners.